PERFORMANCE OF DEEP EXCAVATED RETAINING WALL IN SHANGHAI SOFT DEPOSIT - Z. H. Xu; W. D. Wang; J. H. Wang; S. L. Shen (International Association of Lowland Technology, 2005)
This paper presents a field case of deep excavated pit of a building foundation in soft deposit of Shanghai lowland area. The details of the project are described at first. Then, the design method and construction process are presented. The wall displacements, axial force of struts, and displacement of the steel lattice columns were monitoredand the results are presented and compared with the calculated results in design. Field measured data show that the ratio between the maximum lateral displacement and the excavated depth was controlled within 0.62%. Monitored data also show that the axial force in the second level struts was the largest among the three levels struts while the axial force in the first level strut was the smallest. The design method described in this paper is used to predict the diaphragm wall deformations. The prediction is consistent well with the measured data. However, there are some discrepancies of the axial forces in the struts between the calculated values and the measured values. Factors affecting effectiveness of the supporting system were investigated. The larger the thickness of the wall and the larger the stiffness of the struts, the smaller displacement of the wall will result. The rate of reduction of the wall displacement decreases with the increaseof the thickness of the wall and the stiffness of the struts. There exists a threshold value of the depth ratio of the diaphragm wall, which has a significant influence on the lateral displacement. In this field case the threshold value of depth ratio is 0.3.